Progress report on feed business in Debre Berhan, Doyogena, and Bonga within the SI-MFS and SAPLING initiatives in Ethiopia - Rudiger, Udo; Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2024)
The report documents consultations made with all relevant feed processing stakeholders in ICARDA small-scale feed processing project sites about the progress and challenges faced in the feed business development.